(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A simple and low cost spectrophotometric method was proposed for the determination of Hg (II) in trace amounts using azo ligand derivative from 4,5-bis(4-methoxyphenyl) imidazole as spectrophotometer reagent. The proposed method is based upon the chelation of Hg (II) with the novel azo ligand, the formed violet complex has a maximum absorption at 546 nm. The mole ratio of the complex was 1:2 (metal:ligand). The reaction obeys Beer`s-Lambert law in the concentration range of (0.5-10) μg mL-1. The limit of detection LOD and the limit of quantification LOQ were 0.190 and 0.634 μg mL-1. The molar absorptivity and sandell’s sensitivity are 7.963 ×10+3 L mol-1 cm-1 and 0.025 μg cm-2, respectively. The relative standard deviation RSD% for (n=10) was 1.607%. The interfering effect of cations and anions was studied. The azo compound and its Hg (II) complex were investigated for their biological activity.